The European Unemployment Dilemma - Lars Ljungqvist; Thomas J. Sargent (The Research Institute of Industrial Economics (IUI), 1997)
Post World War II European welfare states experienced several decades of relatively low unemployment, followed by a plague of persistently high unemployment since the 1980s. We impute the higher unemployment to welfare states' diminished ability to cope with more turbulent economic times, such as the ongoing restructuring from manufacturing to the service industry, adoption of new information technologies and a rapidly changing international economy. We use a general equilibrium search model where workers accumulate skills on the job and lose skills during unemployment.
Keywords: E24; J64; 330; Unemployment; Economic turbulence; Welfare state; Europe